The effect of an inhaled glucocorticoid on the degree and rate of orthodontic tooth movement and relapse in mice - Escultura, Ethel L.
In orthodontic tooth movement, alveolar bone remodeling is not only affected by local forces but also by the general metabolic status of skeleton. Some medical problems as well as medications can adversely affect the bone structures. Inhaled glucocorticoids, which are most effective in asthma treatment, are prescribed more commonly now because their adverse effects are considered to be significantly less than the oral and parenteral kinds. The purpose of this study is to determine the effect of an inhaled glucocorticoid on bone and to establish whether or not it influences the degree and rate of orthodontic tooth movement and relapse in mice. In this study, male and female adult mice were administered with a high dose (250 ug/ml) budesonide inhalation suspension prior to the attachment of an orthodontic appliance (experimental subjects). While control mice subjects were directly affixed with the appliance. The molar tooth movement and relapse values determined on Day 4, Day 7, Day 11, Day 14 and Day 18, using a digital caliper. The results of the experiment are the following: (1) For both male and female treatment and control mice subjects, the mean tooth movement values of both groups differed significantly on Day 4 demonstrating increased rates of tooth movement in the male and female treatment groups than in the control groups. (2) In the female control group, the rate of tooth movement was greater when compared to the treatment group on Day 7. (3) On Day 4, the rate of tooth movement was faster in the female treatment group, while on Day 7, the rate of tooth movement was faster in the female control group. (4) A test for the comparison of the mean tooth movement of the male and female treatment groups showed no significant difference on Day 4. (5) In both the male and female subjects, greater amount of relapse was observed in the treatment groups than I the control groups four days after dislodgement of the orthodontic appliance. (6) Some of the male and female treatment subjects displayed more mesial or forward movement of the first molar, even in the absence of the orthodontic appliance, during the relapse observation phase. In conclusion, it was demonstrated that the mice subjects treated with high dose inhaled glucocorticoid for a short period experienced imbalance in the bone remodeling process during orthodontic appliance wear that resulted to a less stable tooth position.